Epidermodysplasia verruciformis with Hansen′s disease, herpes simplex labialis and multiple eccrine hidradenoma - Padmavathy L; Rao L; Ethirajan N; Krishnaswamy B; Manohar U (Wolters Kluwer Medknow Publications, 2009)
Epidermodysplasia verruciformis (EV) - a rare, lifelong heritable disease due to a unique susceptibility to human papilloma virus. The disseminated verrucous lesions or pityriasis versicolor like lesions persist from early childhood and can transform into a cutaneous malignancy in a fourth of patients. The association of EV with multiple eccrine hidradenoma, herpes simplex labialis and Hansen′s disease is a very rare occurrence and is reported in a 25-year-old woman.